Dietary changes and histophysiological responses of a wild fish (Geophagus cf. proximus) under the influence of tilapia cage farm - Kliemann, Bruna Caroline Kotz [UNESP]; Delariva, Rosilene Luciana; Amorim, João Paulo de Arruda; da Silva Ribeiro, Cristiéli [UNESP]; da Silva, Bruno [UNESP]; Silveira, Rosicleire Veríssimo [UNESP]; Ramos, Igor Paiva [UNESP] (Elsevier, 2018)
The influence of cage fish farm on the trophic, histopathological and metabolic aspects of a wild fish species (Geophagus cf. proximus) was evaluated considering diet, liver histopathology and the concentration of total proteins in the liver, gonads and muscles in fish from two sampling areas (cage farm and control). Diet composition and trophic niche breadth differed significantly between the sampling areas. Detritus, aquatic plants and Cladocera composed the diet in the control area, while mollusks and pelleted feed, followed by detritus, were highly representative of the diet of fish in the cage farm area. More severe histopathological alterations were found in the specimens collected in the cage farm area. These alterations include severe pancreatic hyperplasia and hepatic steatosis. Total protein concentrations in muscles showed no significant difference between the areas. For the liver, the highest concentration was found in fish from the cage farm area, whereas for gonads, higher values were detected in the fish from the control area. These results show that there were hepatic and gonadal metabolic changes in farm-associated specimens compared to specimens from the control area. The high protein and lipid contents of the diet promoted severe histopathological alterations in the liver, impairing hepatic function and possibly interfering in the mobilization of proteins to the gonads. Thus, the relationship between dietary changes and histophysiological alterations suggests an influence of cage fish farm on the ecology of farm-aggregated fish species.
Keywords: Aquaculture; Environmental influence; Histopathology; Metabolism; Trophic ecology